Signaling Specific Skills and the Labor Market of College Graduates - Busso, Matias; Montaño, Sebastián; Muñoz-Morales, Juan (The Review of Economics and Statistics, 2025)
Abstract Using administrative data and a regression discontinuity design, we study the labor market effects of a government-sponsored award given to top-performing students on Colombia’s national college exit exam. The award signals field-specific skills, leading recipients to earn seven to ten percent more than comparable peers without the signal. The benefits are concentrated among graduates from lowerreputation institutions, who enter the market with weaker signals and gain access to better job matches and higher-paying firms. These returns persist for up to five years, driven by an upward shift in the intercept of the wage-experience profile of those with weaker signals.